CLUSTER APPROACH IN TEACHING FOREIGN LANGUAGES IN PRE-TERTIARY EDUCATION - Ch. A. Adilova (Galaxy International Interdisciplinary Research Journal, 2023)
The article provides a brief overview of the newly developing cluster approach in teaching foreign languages and gives methodological instructions on preparing different types of exercises to improve students’ professional communicative abilities in foreign languages using authentic materials.